Genomic Analysis of Hair Sheep From West/Central Africa Reveals Unique Genetic Diversity and Ancestral Links to Breed Formation in the Caribbean - Pamela Wiener; Juliane Friedrich; Melissa M. Marr; Gustave Simo; Vincent N. Tanya; Keith T. Ballingall; Pavel Flegontov; Benjamin D. Rosen; Guillaume Sallé; Gordon Spangler; Curtis P. Van Tassell; Mazdak Salavati; et al. (Molecular Ecology, 2025)
Cameroon Blackbelly sheep are a domestic breed of hair sheep from West/Central Africa. They are popular with small‐holder farmers in Cameroon as they are highly resilient to local environmental challenges and are prolific a‐seasonal breeders. The aim of this study was to characterise the genetics of Cameroon Blackbelly sheep in relation to global sheep populations and to investigate their relationship to Caribbean hair sheep. We first examined the genetic diversity of the Cameroon Blackbelly breed relative to global sheep populations using 50K SNP data. We also used whole genome sequence data to further investigate relationships between Cameroon Blackbelly and breeds from Africa and Europe, as well as the Barbados Blackbelly breed from the Caribbean, which is phenotypically similar to Cameroon Blackbelly. ADMIXTURE results based on 50K and WGS data demonstrated both West/Central African and European ancestries for the Barbados Blackbelly sheep. Results from f 4 ‐statistics‐based qpAdm analyses supported these findings. Local ancestry inference identified several genomic regions in Barbados Blackbelly with high proportions of West/Central African ancestry. One of these, on OAR3, includes various keratin genes, suggesting that these genes may play a role in the shared coat phenotypes of the Barbados Blackbelly and Cameroon Blackbelly. This result is consistent with previous reports of adaptive introgression of coat characteristics in both wild and domesticated species. The findings of our study support the view that sheep were transported from West/Central Africa to the Caribbean as part of the transatlantic slave trade and European colonisation, similar to introductions proposed for cattle and goats.